Friendship trust and psychological well-being from late adolescence to early adulthood: A structural equation modelling approach. Issue 3 (May 2017) - Miething, Alexander; Almquist, Ylva B.; Edling, Christofer; Rydgren, Jens; Rostila, Mikael
Aims: This study explored the sex-specific associations between friendship trust and the psychological well-being of young Swedes from late adolescence to early adulthood. Methods: A random sample of native Swedes born in 1990 was surveyed at age 19 years and again at age 23 years regarding their own well-being and their relationships with a maximum of five self-named peers. The response rate was 31.3%, resulting in 782 cases to be analysed. We used sex-stratified structural equation models to explore the associations between trust and well-being. Psychological well-being was constructed as the latent variable in the measurement part. The structural part accounted for the autocorrelation of trust with respect to well-being over time and incorporated the cross-lagged effects between late adolescence and early adulthood. Results: It was found that trust increased while well-being decreased for young men and remained stable for young women from 19 to 23 years of age. The young women reported lower well-being at both time points, whereas no sex difference was found for trust. Based on model fit comparisons, a simple model without forward or reward causation was accepted for young men, whereas reversed causation from well-being to trust was suggested for young women. Subsequent analysis based on these assumptions confirmed the reversed effect for young women. Conclusions: The findings suggest that young people do not benefit from trustful social relations to the same extent as adult populations. Young women who express impaired well-being run a greater risk of being members of networks characterized by low friendship trust over time.